Cementitious, Pozzolanic And Filler Materials For DSM Binders - John Kok Hee Wong; Sien Ti Kok; Soon Yee Wong (Salehan Institute of Higher Education, 2020)
Deep Soil Mix (DSM) is a proven method of ground improvement for deeper underlying soft soil layers which are otherwise impractical to reach using conventional shallow soil stabilization and replacement methods. The predominant binder materials used are Ordinary Portland cement (OPC) and Lime (CaO) but negative effects to the environment from manufacture and increasing construction cost have prompted research into alternative materials. This review identifies pozzolans and filler materials as possible supplements or partial substitutes for better results. The DSM method and binder reaction processes during treated soil strength development are outlined and effectiveness of different pozzolans (Fly Ash, Silica Fume, Ground Granulated Blast Furnace Slag, Rice Husk Ash, Kaolin, and Metakaolin) and filler materials (e.g. fine sand) discussed together with their influence factors. With many pozzolans, a clear optimum dosage is observed where improved strength peaks. Aluminosilicate pozzolans perform better over siliceous pozzolans with Metakaolin (MK) identified as the most effective pozzolan for enhancing compressive strength. Up to date research results on these materials are compiled. MK blended cements are readily available and can be readily applied for initial field tests. Treated soil strength may be regulated with addition of filler materials to further reduce reliance on cement.